`Mind' as humanizing the brain: Toward a neurotheology of meaning. - Ashbrook, James B. (Zygon: Journal of Religion & Science)
Provides information on a study relating to the concept of `mind' mainly focusing on the biblical and philosophical perspectives. Information on mosaic of meanings of mind; Conclusion reached.